Analysis of the Circular Transcriptome in the Synaptosomes of Aged Mice. (21st November 2020) - Curry-Hyde, Ashton; Ueberham, Uwe; Chen, Bei Jun; Zipfel, Ivonne; Mills, James D.; Bochmann, Jana; Jendrek, Renate; Takenaka, Konii; Kirazov, Ludmil; Kirazov, Evgeni; Jünger, Jennifer; Brückner, Martina K.; et al.
Highlights: Circular RNAs accumulate in aged synaptosomes as compared to young synaptosomes. Experimental validation confirmed five circRNAs specifically expressed in young and aged synaptosome. CircRNAs show distinct expression pattern in synaptosomes as compared to neuronal homogenates. We identified 16 genes expressing circular RNA transcripts which do not express linear RNA transcripts in synaptosomes. Abstract: Recently, circular RNAs (circRNAs) have been revealed to be an important non-coding element of the transcriptome. The brain contains the most abundant and widespread expression of circRNA. There are also indications that the circular transcriptome undergoes dynamic changes as a result of brain ageing. Diminished cognitive function with increased age reflects the dysregulation of synaptic function and ineffective neurotransmission through alterations of the synaptic proteome. Here, we present changes in the circular transcriptome in ageing synapses using a mouse model. Specifically, we observed an accumulation of uniquely expressed circular transcripts in the synaptosomes of aged mice compared to young mice. Individual circRNA expression patterns were characterized by an increased abundance in the synaptosomes of young or aged mice, whereas the opposite expression was observed for the parental gene linear transcripts. These changes in expression were validated by RT-qPCR. We provide the first comprehensive survey of the circular transcriptome in mammalian synapses, thereby paving the way for future studies. Additionally, we present 16 genes that express solely circRNAs, without linear RNAs co-expression, exclusively in young and aged synaptosomes, suggesting a synaptic gene network that functions along canonical splicing activity.